Room Security System Design using ESP32 CAM with Fuzzy Algorithm - Putra, Wahyu Sukestyastama; Andy Setyawan (Mobile and Forensics, 2021)
At this time, security becomes an important thing that must be fulfilled. Especially a room that has valuables. Currently, the average room security only uses conventional methods, which are very easy to break. Therefore, An Intelligent security system is needed to maintain security in a room. An Intelligent security system is a system that can detect everything automatically and can be monitored remotely using the internet or better known as IoT (Internet of Things). This system uses a microcontroller as the primary part of running the system and is supported by several modules such as the PIR infrared motion sensor module, door window magnetic sensor module, camera module, and buzzer alarm module. The door & window magnetic sensor module serves as the first security, which, when the door/window is open, will give a warning via the buzzer alarm module. While the PIR infrared motion sensor module functions as second security which if motion is detected in a room, it will trigger the camera module to take pictures in the room. The results of this system will be sent directly to Android via the Telegram application using a bot. This Telegram bot will send data in text and images from the system to Android directly.